Toward a RESTful Information-Centric Web of Things: A Deeper Look at Data Orientation in CoAP - Cenk Gündogan; Christian Amsüss; Thomas Schmidt; Matthias Wählisch (ACM Conference on Information-Centric Networking 2020, 2020)
The information-centric networking (ICN) paradigm offers replication of autonomously verifiable content throughout a network, in which content is bound to names instead of hosts. This has proven beneficial in particular for the constrained IoT. Several approaches, the most prominent of which being Named Data Networking, propose access to named content directly on the network layer. Independently, the IETF CoAP protocol group started to develop mechanisms that support autonomous content processing and in-network storage. In this paper, we explore the emerging CoAP protocol building blocks and how they contribute to an information-centric network architecture for a data-oriented RESTful Web of Things. We discuss design options and measure characteristic performances of different network configurations, which deploy CoAP proxies and OSCORE content object security, and compare with NDN. Our findings indicate an almost continuous design space ranging from plain CoAP at the one end to NDN on the other. On both ends - -ICN and CoAP - -we identify protocol features and aspects whose mutual transfer potentially improves design and operation of the other.
Keywords: CoAP Proxy; content object security; protocol evaluation; OSCORE; Internet of Things; ICN